Validation of a method for estimating pulmonary dead space in ventilated beagles to correct exhaled propofol concentration in mixed air - Xiaoxiao Li; Pan Chang; Xing Liu; Zhongjun Zhao; Yixiang Duan; Wensheng Zhang (BMC Veterinary Research)
Abstract Background Mixed exhaled air has been widely used to determine exhaled propofol concentrations with online analyzers, but changes in dead space proportions may lead to inaccurate assessments of critical drug concentration data. This study proposes a method to correct propofol concentration in mixed air by estimating pulmonary dead space through reconstructing volumetric capnography (Vcap) from time-CO2 and time-volume curves, validated with vacuum ultraviolet time-of-flight mass spectrometry (VUV-TOF MS). Methods Existing monitoring parameters, including time-volume and time-CO2 curves, were used to determine Vcap. The ratio of physiological dead space to tidal volume (VD/VT) was calculated using Bohr’s formula. Additionally, an animal experiment on beagles was conducted with continuous propofol administration until a pseudo-steady state in exhaled propofol concentration was achieved. The propofol concentration in mixed air (CONCmix), and in alveolar air combined with N2 (CONCAN) were measured using VUV-TOF MS to calculate VD/VT. The agreements between VD/VT values from the two methods, along with the predicted CONCAN values based on Vcap and the actual measured CONCAN values were evaluated using the intraclass correlation coefficient (ICC) and Pearson correlation analysis. Results After 30 min of continuous propofol administration, a stable respiratory cycle was selected for analysis in each beagle. The calculated VD/VT-Bohr values were 0.535 for beagle A, 0.544 for beagle B, and 0.552 for beagle C. Additionally, based on CONCmix and CONCAN, the calculated VD/VT-VUV-TOF MS values were 0.494, 0.504, and 0.513, respectively. Strong agreement between the two methods was demonstrated by an ICC of 0.994 (P = 0.003) and Pearson’s r of 0.995 (P = 0.045). Additionally, the predicted CONCAN values from mixed exhaled air (5.11 parts per billion by volume (ppbv) for beagle A, 5.93 ppbv for beagle B, and 2.56 ppbv for beagle C) showed strong agreement with the actual CONCAN values, with an ICC of 0.996 (P = 0.002) and Pearson’s r of 0.994 (P = 0.046). Conclusion The physiological dead space to tidal volume ratio from mixed air in beagles can be accurately measured using the existing time-volume and time-CO2 curves from the anesthesia machine, enabling corrections of exhaled propofol concentrations in mixed air samples.